The Influence of Corporate Social Responsibility on Customer Loyalty Across Countries - Marcelia Adriana Batuwael; Ataina Rusyda Fauziyah; Hwihanus Hwihanus (CV. Lenggogeni Data Publishing, 2024)
Corporate Social Responsibility (CSR) is an organization's responsibility for the impact of its decisions and activities on society and the environment, through transparent and ethical behaviour that contributes to sustainable development, including the health and welfare of society; consider stakeholder expectations; comply with applicable laws and be consistent with international norms of behaviour; and integrated throughout the organisation and practised in its relations. Companies' corporate social responsibility (CSR) efforts can be influenced by a variety of variables. There are firms that focus on CSR as a way of giving back to society (community development), while others see it as a type of corporate giving/charity and continual improvement, with the goal of improving the company's image. The purpose of this study is to synthesise previous research on the impact of Corporate Social Responsibility (CSR) on consumer loyalty in various nations. This study employed a meta-analysis method combined with a qualitative approach. Based on the findings, the author concludes that effective Corporate Social Responsibility can boost customer loyalty through a variety of methods, including improved reputation, image, satisfaction, trust, and customer commitment.